Alleviation of cold stress in vegetable crops - Atayee, Abdul Rasool; Noori, Mohammad Safar (Journal of Scientific Agriculture, 2020)
Low temperature is a major environmental factor that limits crop productivity of plants. Cold stress is a serious threat to the sustainability of crop yields. Low temperature has a huge impact on the survival and geographical distribution of plants. It negatively affects cellular components and metabolism, and temperature extremes impose stresses of variable severity that depend on the intensity and duration of the stress. Low temperature (less than minimum) leads to chlorosis, necrosis, membrane damage, changes in cytoplasm viscosity, and changes in enzyme activities leading to death of plant. Cold stress disrupts the integrity of intracellular organelles, leading to the loss of compartmentalization. It also causes reduction and impairing of photosynthesis, protein assembly and general metabolic processes. Moreover, cold stress during anthesis induces flower dropping, sterility of pollen, pollen tube distortion, ovule abortion and reduced fruit set, which leads to declined growth and lower yield. A number of approaches are being used to mitigate the deleterious effects of cold stress which threatens the successful vegetable crop production, application of plant growth regulators (salicylic acid, abscisic acid, jasmonic acid, Gibberellin and brassinosteroids) and unitization of genetics tools and plant breeding is one of the strategies to alleviate the low temperature stress in vegetable crops. Plant growth regulators play a greater role in improving the cold stress tolerance. In this paper, the effects of cold stress on vegetable growth, productivity and physiological activities were discussed, and some effective techniques for the mitigation of cold stress that help sustainable vegetable production under fluctuating climate is presented.